2005
DOI: 10.1002/adma.200400648
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Inverse Opals Fabricated Using Low‐Temperature Atomic Layer Deposition

Abstract: Following the work of John [1] and Yablonovitch, [2] the study of photonic crystals (PCs) has become an important area of research for applications in optoelectronics and electromagnetics, as well as chemical and biological sensors. Formation of a complete photonic bandgap (PBG) requires a three-dimensional (3D) periodic structure exhibiting high refractiveindex contrast. PCs based on infiltration of self-assembled opals are promising structures, [3±5] and a full PBG at infrared wavelengths has been produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(189 citation statements)
references
References 24 publications
(15 reference statements)
7
175
0
5
Order By: Relevance
“…In addition, creating high-aspect ratio nanostructures via dry etching of TiO 2 , similar to other dielectric materials, is difficult and can lead to increased sidewall roughness. This ALD process is different from previous techniques (24,25) where the patterns created are generally fixed by a set template (e.g., anodic alumina or inverse opal). Here we are free to define more complex nanostructures because we use ALD directly on exposed EBR.…”
mentioning
confidence: 99%
“…In addition, creating high-aspect ratio nanostructures via dry etching of TiO 2 , similar to other dielectric materials, is difficult and can lead to increased sidewall roughness. This ALD process is different from previous techniques (24,25) where the patterns created are generally fixed by a set template (e.g., anodic alumina or inverse opal). Here we are free to define more complex nanostructures because we use ALD directly on exposed EBR.…”
mentioning
confidence: 99%
“…From our previous work, an opal infiltration growth rate of 0.51 Å/cycle was used to estimate the thicknesses of the infiltrated TiO 2 . 15 The evolution of the reflectivity spectra during formation of the non-close-packed structure is shown in Figures 13 and 14, after 160, 280, 400, and 520 ALD cycles.…”
Section: Non-close-packed Inverse Opalsmentioning
confidence: 99%
“…Thus, for the growth of TiO 2 , using a custom-built, flow-style, hot-wall ALD reactor, special protocols were developed to obtain high conformity and optimum crystallinity, and to address the requirements of depositing material within a highly porous structure. 15 The initial studies on the growth of the high index rutile phase of titania on planar substrates showed that even for growth temperatures above 600 o C, it was difficult to reproducibly form the rutile phase and that the resulting polycrystalline films exhibited considerable surface roughness which increased with deposition temperature. 16 However, as shown by Figure 1, by significantly decreasing the growth temperature (~100 ºC) very low RMS roughness (0.2 nm) films were achieved.…”
Section: Opal Fabricationmentioning
confidence: 99%
“…Temperature variations during ALD-growth have significant influence on the surface roughness e.g., in infiltration of silica opals to fabricate TiO 2 inverse opals with spherical size templates ranging from 200 to 440 nm in diameter show different roughness (King et al, 2005a). Atomic Force Microscopy (AFM) studies shows that TiO 2 films yielded a root-mean-square (RMS) roughness of 0.2 nm at 100°C, 2.1 nm at 300°C, and 9.6 nm at 600°C, which shows that low temperature deposition is of much more significance for even filling and preparing extremely smooth interfaces (King et al, 2005a).…”
Section: Low Temperature Ald-growthmentioning
confidence: 99%